2013
DOI: 10.3382/ps.2012-02509
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic development and the physiological factors that coordinate hatching in domestic chickens

Abstract: Embryonic growth and development is influenced by both endogenous and exogenous factors. The purpose of this review is to discuss the critical stages of chick embryonic development in relation to functional maturation of numerous organ systems, the acquisition of thermoregulation, and the hatching process. In addition, the mechanism of hatching, including sound synchronization and hormonal and environmental stimulation, will be discussed. Finally, the importance of effective hatching synchronization mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 78 publications
1
65
0
3
Order By: Relevance
“…Moreover, corticosterone is also a critical endogenous factor affecting overall embryo metabolism and behavior (Tong et al, 2013). According to Quinteiro-Filho et al (2010) and Tong et al (2013), high corticosterone levels reduce yolk sac absorption rate as well as the weight of bursa, thymus, and spleen, predisposing to lower immunity.…”
Section: Effect Of Embryo Thermal Stimulation On the Serum Levels Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, corticosterone is also a critical endogenous factor affecting overall embryo metabolism and behavior (Tong et al, 2013). According to Quinteiro-Filho et al (2010) and Tong et al (2013), high corticosterone levels reduce yolk sac absorption rate as well as the weight of bursa, thymus, and spleen, predisposing to lower immunity.…”
Section: Effect Of Embryo Thermal Stimulation On the Serum Levels Of mentioning
confidence: 99%
“…Moreover, corticosterone is also a critical endogenous factor affecting overall embryo metabolism and behavior (Tong et al, 2013). According to Quinteiro-Filho et al (2010) and Tong et al (2013), high corticosterone levels reduce yolk sac absorption rate as well as the weight of bursa, thymus, and spleen, predisposing to lower immunity. Rodricks et al (2006) reported that glucocorticoids are essential for energy metabolism, and regulate several neurotransmitter receptors in broilers, and showed that a sharp increase in embryo corticosterone levels due to hypoxia impairs chick memory at hatch.…”
Section: Effect Of Embryo Thermal Stimulation On the Serum Levels Of mentioning
confidence: 99%
“…However, within a normal batch of eggs, the time from the hatching of the first egg to the last can be as much as 36-48 hours (Tong et al, 2013;van de Ven et al, 2011). This time period is called the hatch window.…”
Section: The Hatch Windowmentioning
confidence: 99%
“…During the hatching process, several endocrine axes are involved in preparing the embryo for postnatal life, as well as facilitating hatching behavior (Tong et al, 2013). Inactive thyroxine (T4) and active 3,3′,5-triiodothyronine (T3) both start to increase on day 15 of incubation, but whereas T3 continues to slowly rise until hatch, T4 decreases after internal pipping on day 19 or 20.…”
Section: The Hatch Windowmentioning
confidence: 99%
See 1 more Smart Citation